2012
DOI: 10.1161/circresaha.112.265173
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Scn10a Channels in Heart Reduces Late Sodium Current and Is Antiarrhythmic

Abstract: Rationale While the sodium channel locus SCN10A has been implicated by genome-wide association studies as a modulator of cardiac electrophysiology, the role of its gene product Nav1.8 as a modulator of cardiac ion currents is unknown. Objective We determined the electrophysiological and pharmacological properties of Nav1.8 in heterologous cell systems and assessed the antiarrhythmic effect of Nav1.8 block on isolated mouse and rabbit ventricular cardiomyocytes. Methods and results We first demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(179 citation statements)
references
References 43 publications
5
169
2
3
Order By: Relevance
“…The new I Na description was scaled such that peak current amplitudes during the AP were unaltered. Recent results suggest that Nav1.8 is responsible for the late sodium current in cardiomyocytes 37,39 . We therefore left the existing persistent sodium current of the model unaltered.…”
Section: Methodsmentioning
confidence: 99%
“…The new I Na description was scaled such that peak current amplitudes during the AP were unaltered. Recent results suggest that Nav1.8 is responsible for the late sodium current in cardiomyocytes 37,39 . We therefore left the existing persistent sodium current of the model unaltered.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Subsequently, Nav1.8 expression was demonstrated in mouse and human cardiac myocytes and intracardiac neurons. 16 In cardiac myocytes, block of Nav1.8 reduces late Na C current and shortens action potential duration, 17 while block of Nav1.8 in intracardiac neurons reduces action potential frequency. 18 How these observations relate to cardiac conduction is not entirely clear.…”
Section: Sodium Channelsmentioning
confidence: 99%
“…Compared with SCN5A ‐ SCN3B transfected TSA‐201 cells, the current density was significantly increased and was sensitive to A‐803467 when SCN10A were added together with SCN5A ‐ SCN3B . Since others' and our studies have reported the extremely low current density in SCN10A ‐ SCN3B transfected cell lines,9, 21 it is reasonable to deduce that the increased current is not an arithmetic addition of current component produced by SCN10A . It implies that SCN10A might interact with SCN5A as a new sodium complex (Figure 8), and A‐803467 could have an effect on SCN10A‐SCN5A complex, as indicated in our patch clamp study.…”
Section: Discussionmentioning
confidence: 57%